2012
DOI: 10.1259/bjr/26733491
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the yield of recombinant thyroid-stimulating hormone-stimulated 2-(18-fluoride)-flu-2-deoxy-D-glucose positron emission tomography-CT in patients with differentiated thyroid carcinoma

Abstract: Objective: The aim of this study was to assess the accuracy of recombinant thyroidstimulating hormone (rTSH)-stimulated 2-(18-fluoride)-flu-2-deoxy-D-glucose ( Results: 58 rTSH PET-CT scans were performed in 47 patients with a previous thyroidectomy and radioiodine ablation. The only indication for PET-CT was a raised thyroglobulin level in 46 of 58 scans, with the remainder for characterisation of equivocal radiology or staging. 25 (43%) of PET-CT scans were positive for recurrent disease. Histological correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The literature search identified 34 studies with a total of 2639 patients meeting the inclusion criteria ( 6 , 16 48 ). Eleven studies reported on the diagnostic accuracy of single-modality PET, 17 on PET/CT, and six on both PET and PET/CT (“mixed”).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search identified 34 studies with a total of 2639 patients meeting the inclusion criteria ( 6 , 16 48 ). Eleven studies reported on the diagnostic accuracy of single-modality PET, 17 on PET/CT, and six on both PET and PET/CT (“mixed”).…”
Section: Resultsmentioning
confidence: 99%
“…Whether or not PET/CT with 18 F-FDG in DTC should be performed under TSH stimulation remains a controversial issue. In our retrospective analysis, we included only patients who underwent PET/CT under TSH stimulation, as it has been reported that TSH stimulation not only influences PET/CT's sensitivity, but also significantly affects its impact on clinical management [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…19,20 However, a lower sensitivity in the diagnostic accuracy of 18F-FDG-PET/PET-CT imaging after rhTSH stimulation was observed in the suspected recurrent thyroid cancer patients with low titer of thyroglobulin. 20 In this set of patients, the utility of rhTSH stimulation procedure could lie in the identification of patients with low stimulated Tg serum levels: consequently, the assessment of Tg serum level after rhTSH stimulation is potentially useful in identifying patients unlikely to benefit from an 18 F-FDG-PET-CT. 21 Finally, there are other interesting points that emerge from analyzed literature. First, a previously good quality conventional imaging raised the sensitivity in the detection of recurrent thyroid cancer of 18 F-FDG-PET-CT. Second, a direct correlation between SUV (standardized uptake value) max and cervical lymph-nodes size was observed.…”
Section: Pet-ct In Differentiated Thyroid Carcinomamentioning
confidence: 97%
“…In this set of patients, the utility of rhTSH stimulation procedure could lie in the identification of patients with low stimulated Tg serum levels: consequently, the assessment of Tg serum level after rhTSH stimulation is potentially useful in identifying patients unlikely to benefit from an 18 F-FDG-PET-CT. 21 …”
Section: Pet-ct In Differentiated Thyroid Carcinomamentioning
confidence: 99%